LEACHING EFFECTS ON SOME PROPERTIES OFSANDY GYPSEOUS SOILS - A. Ahmed Al-Sharrad, Muayad (Iraqi Journal of Civil Engineering, 2007)
A BSTRACT: Leaching effects on permeability and compressibility characteristics of undisturbed sandy gypseous soil were investigated in this study. Time, stress level, strain, leachate condition and flow velocity were considered. The loading, leaching and permeability measurements were carried out utilizing the constant head pereameter with special modifications. Test results show that salt leaching and thereby leaching strain is a time dependent process. Also as leaching strain continued coefficient of permeability decreases.